1678 Historical perspectives on occupational health in ireland. (24th April 2018) - D Blanc, Paul; Menendez-Navarro, Alfredo; Hayes, J; Evans, AE; Addley, K; Malone, JM
Abstract : Aim of special session: This session will address the Irish perspective on the history of occupational disease.